Analisis Semiotika Roland Barthes Pidato Gibran Rakabuming Raka dalam Deklarasi Sebagai Cawapres 2024 pada Breaking News Kompas TV - Sendy Apriliansyah; Makroen Sanjaya (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Gibran Rakabuming Raka's declaration speech as Vice President 2024 should be communicatively easy to understand by the general public, the meaning conveyed must be of quality, but at the time of the declaration as Vice President 2024 Gibran Rakabuming Raka in his speech contained multiple interpretations or difficult to understand by the public. The purpose of this study is to analyze the meaning of Denotation. Connotations and Myths. Gibran Rakabuming Raka's speech in his declaration as Vice President 2024 on Breaking News Kompas TV. Theories used are Mass Communication, Television, Breaking News, Broadcasting, Semiotics and Semiotics Roland Barthes. The research approach is qualitatively descriptive, with data collection using primary data, secondary data, analysis, interviews and documentation. This study uses Roland Barthes's Semiotic Analysis method, covering 3 meanings namely Denotation. Connotations and Myths. The results obtained in this study Gibran's speech in his declaration as President 2024 on the Breaking News program Kompas TV have three meanings: Denotation: Winning and continuing the old program. Connotations: Gibran is a staunch supporter of Prabowo and a leader with a vision of sustainability. Myth: Solidarity with Prabowo, continuity of leadership and hope of the younger generation.